Geomorphic analysis of the Middle Rio Grande - Elephant Butte Reach, New Mexico - Owen, Tracy Elizabeth, author; Julien, Pierre, advisor; Thornton, Christopher, committee member; Rathburn, Sara, committee member (Colorado State University. Libraries, 2012)
The Elephant Butte Reach spans about 30 miles, beginning from the South Boundary of the Bosque del Apache National Wildlife Refuge (River Mile 73.9) to the "narrows" of the Elephant Butte Reservoir (River Mile 44.65), in central New Mexico. Sediment plugs occasionally form along the Middle Rio Grande, completely blocking the main channel of the river. In 1991, 1995, and 2005, the Tiffany Plug was initiated at the upstream end of the Elephant Butte Reach. In 2008, the Bosque del Apache Plug formed just upstream of the Elephant Butte Reach. Sediment plugs occur at the location of a constriction or channel aggradation (Burroughs 2011). As aggradation within the Elephant Butte Reach is known to contribute to a decrease in channel capacity (Reclamation 2007), it is important to understand the influences of Elephant Butte Reservoir levels on channel aggradation/degradation in order to decrease the potential for future sediment plug formation. Further understanding of the historical and spatial changes within Elephant Butte Reach, along with a better understanding of the influences of Elephant Butte Reservoir levels on channel aggradation/degradation, are essential for improvement in future river management practices along the Middle Rio Grande. Using aerial photographs, survey data, reservoir water surface elevation data, and bed material data, the following objectives are addressed in this study: 1. Quantify temporal changes in channel widths and sinuosity from 1935 to 2010. 2. Quantify change in channel slope temporally. 3. Quantify rate of aggradation/degradation in response to a change in base-level (i.e., change in reservoir water surface elevation). 4. Quantify aggradation/degradation wave propagation upstream. 5. Quantify spatial and temporal trends in bed material grain size. From 1935 to 2010, channel widths and sinuosity decrease over time. The majority of the Reach's channel slope decreases from 1935 to 2010; the downstream-most stretch of the channel, closest to Elephant Butte Reservoir, alternates between increasing and decreasing channel slopes. As the Elephant Butte Reservoir level (base-level) increases, the channel aggrades in response. As the base-level decreases, the channel degrades. The rates of aggradation and degradation vary between different periods of base-level changes, and are quantified within the report. When the base-level changes a wave of aggradation/degradation travels upstream. The rate of wave propagation upstream varies relative to the rate of base-level change, and is quantified within the report for four sets of aggradation/degradation waves. Bed material samples obtained from cross-section surveys and at the San Acacia and San Marcial gauges showed a coarsening at a rate of about 0.03 mm/year. In the downstream direction, bed material became slightly finer. The median bed material grain size ranged from 0.11 mm to 0.26 mm.
Keywords: degradation; geomorphology; Elephant Butte Reach; aggradation; base-line change; Rio Grande